Peningkatan Kemampuan Motorik Kasar dalam Permainan Tradisional Roda Gelinding di Ra Syafawil Jannah Turen-Malang - Yulia, Nikmahtul Khoir Tri; Muaffah, Fitrotul (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Pesantren Mathali'ul Falah Pati, 2023)
This research is motivated by the activities carried out at RA Syafawil Jannah tend to be boring and less attractive, so children are less able to walk in a straight line on the boardwalk, lack concentration and coordinate between eyes and feet, by playing traditional children's rolling wheelsThe purpose of the study was to describe the process of children's gross motor skills and the results of increasing gross motor skills through rolling wheel games in group B. This study uses classroom action research (CAR) with the research subjects of children in group B at RA Syafawil Jannah Turen. The focus of this research was carried out with 2 cycles, The success rate in each cycle of children's gross motor physical abilities in traditional games includes cycle I consisting of (I) meetings as much as 41.7%, (II) 50%, (III) 58%, and in cycle II it reaches (I) 66, 8%, (II) 75%, (III) 83.3%. The results of the increase between the last meeting in each cycle reached a percentage of 25.3% which was categorized as good for increasing gross motor skills. It is hoped that traditional games can be introduced to children in a more creative and innovative way with the aim of preserving local wisdom in Indonesia.